1982
DOI: 10.1042/bj2040593
|View full text |Cite
|
Sign up to set email alerts
|

Spin-trapping studies on the free-radical products formed by metabolic activation of carbon tetrachloride in rat liver microsomal fractions isolated hepatocytes and in vivo in the rat

Abstract: 1. The metabolic activation of carbon tetrachloride to free-radical intermediates is an important step in the sequence of disturbances leading to the acute liver injury produced by this toxic agent. Electron-spin-resonance (e.s.r.) spin-trapping techniques were used to characterize the free-radical species involved. 2. Spin trapping was applied to the activation of carbon tetrachloride by liver microsomal fractions in the presence of NADPH, and by isolated intact rat hepatocytes. The results obtained with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(52 citation statements)
references
References 22 publications
5
47
0
Order By: Relevance
“…These results have now been confirmed by other laboratories (39,40). It was also demonstrated that the trichloromethyl radicals apparently are generated in rat liver microsomes by only one form of cytochrome P-450 (41,42 rapidly and essentially disappears within 1 hr.…”
Section: Biochemistry and Halocarbon Radical Formation In Vitro Invessupporting
confidence: 77%
See 1 more Smart Citation
“…These results have now been confirmed by other laboratories (39,40). It was also demonstrated that the trichloromethyl radicals apparently are generated in rat liver microsomes by only one form of cytochrome P-450 (41,42 rapidly and essentially disappears within 1 hr.…”
Section: Biochemistry and Halocarbon Radical Formation In Vitro Invessupporting
confidence: 77%
“…2(CH3)3COO-(CH3)3COOOOC(CH3)3 (38) (CH3)3COOOOC(CH3)3 --2(CH3)3CO + 02 (39) 0 (CH3)3CO -> CH3-+ CH3-C-CH3 (40) Superoxide can be made electrochemically by reduction of oxygen and subsequently reacted with the halocarbon (19,25,26). Sawyer and co-workers (5,25,26) have published some studies on compounds with the trichloromethyl group performed in this manner.…”
Section: Superoxide Anion Reductionmentioning
confidence: 99%
“…Also, kaempferol is a very good scavenger, even though it only has one hydroxyl group on the B ring (4′-OH), possibly due to the combination of other characteristics such as, a C2-C3 double bond, 3-OH group, and 4-keto group on ring C (Van Acker et al, 1996. The mechanism of antiradical action of quercetin and its glycoside was evaluated by Afanas'ev et al (1989) and Albano et al (1982) who referred the inhibitory effects of both quercetin and rutin to their ability to ameliorated the damage occurred by CCl 4 -dependent lipid peroxidation in rat liver microsomes. Therefore, the data reported herein reveal a protective potential of quercetin and kaempferol glycosides, the main constituents of F. carica leaf, against the acute hepatotoxicity induced by CCl 4 in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular toxicity of CCl 4 requires activation by the liver microsomal mixed function oxidase (CYP 2E1) to produce trichloromethyl radical (CCl 3 . ) (Albano et al, 1982). In the presence of oxygen, however, CCl 3…”
Section: Introductionmentioning
confidence: 99%